(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article analyzes some characteristics of two Brazilian criminal organizations – Primeiro Comando da Capital (PCC) [First Command of the Capital] and Comando Vermelho (CV) [Red Command]. It addresses the context of social inequalities and the aspects that allow the reproduction of these groups through drug trafficking, incarceration, and their actions beyond crime in communities.